math
posted by anonymous .
A sequence of polynomials gk(x) is defined recursively as follows.
g0(x)=x; gk+1(x)=gk(x^2+2x)−gk(x)
Find the last three digits of the coefficient of x^2 in g299(x).

941

sorry, but wrong answer...
repeating the question again >
A sequence of polynomials gk(x) is defined recursively as follows:
g0(x)=x
gk+1(x)=gk(x^2+2x)−gk(x)
Find the last three digits of the coefficient of x^2 in g299(x). 
634

That's wrong. I thint, that should be 925.
Respond to this Question
Similar Questions

Math sequence
Let {An} be the sequence defined recursively by A1=sqr(2) and A(n+1) = sqr(2+An) for n is bigger and equal to 1. Show that An < 2. What is An? 
Discrete Math
Calculate R(4) where the recursively defined sequence R is given by: R(1) = 2, R(2) = 3, and, R(n) = R(n − 1) + 2R(n − 2) + n, n > 2 
algebra 2
A sequence is defined recursively by a1=1,an=(an1+1)^2. Write the first 4 terms of the sequence. 
Discrete Mathematics
Suppose a0, a1, a2 ,... is a sequence defined recursively as follows: a1 = 1, a2 = 2, a3 = 3 and ak = ak1 + ak2 + ak3 for all integers k > 3. Use strong induction to show that an < 2n for all integers n ≥ 1. 
precalculus
Find the first five terms of the given recursively defined sequence. an = 3an − 1 + 9 and a1 = 2 
Fibonacci sequence
The Fibonacci sequence a1=1,a2=1,a3=2,a4=3,a5=5,a6=8… is defined recursively using the formulas a1=a2=1 and an+2=an+an+1 for all n≥1. Find the greatest common divisor of a484 and a2013. 
Urgent math
Find the first five terms of the given recursively defined sequence. an = 3an − 1 + 6 and a1 = 1 a1= a2= a3= a4= a5= 
Math
this is a difficult question for me please help! thankyou A sequence is defined recursively by an + 1 = 3an − n, a1 = 2. Find the first six terms of the sequence. a1 = a2 = a3 = a4 = a5 = a6 = 
math asap
this is a difficult question for me please help! thankyou A sequence is defined recursively by an + 1 = 3an − n, a1 = 2. Find the first six terms of the sequence. a1 = a2 = a3 = a4 = a5 = a6 = 
math
Write the first five terms of the sequence defined recursively. Use the pattern to write the nth term of the sequence as a function of n. (Assume that n begins with 1.) a (subtext) 1 =4,a (subtext) (k+1) =−a (subtext) k a. a …